Comparação entre instrumentos de avaliação da habilidade motora oral de recém-nascidos pré-termo para a introdução da alimentação por via oral - Prade, Leila Sauer (2017)
This research aimed to compare instruments for the evaluation of oral motor skills in preterm newborns in order to verify the readiness to start oral feeding and the oral feeding transition through the following protocols: Preterm Oral Feeding Readiness Scale - POFRAS; Non-Nutritive Suction Evaluation Protocol and Neonatal Oral-Motor Assessment Scale - NOMAS. To correlate with oral feeding skill, by proficiency, rate of milk transfer, overall transfer (OT), during the introduction of the first oral feeding, and time of transition required for the complete transition from start to independent oral feeding. To check which of these best instruments identifies oral feeding skill in addition to observing the signs of stress. Seventy-one PTNB with a gestational age of less than 34 weeks, clinically stable, who were receiving 70 ml/kg/day at the time of the evaluation and who met the study criteria were enrolled. The PTNB were evaluated at the first oral feeding by a single evaluator with certificate for application of the NOMAS protocol, and after evaluation, each newborn received a classification with or without readiness to start oral feeding, according to each protocol. PTNB with readiness by NOMAS had higher values of proficiency and rate of milk transfer and attained independent oral earlier. Signs of stress were lower in premature infants with readiness. NOMAS showed higher positive and negative predictive value in relation to the other two instruments and it was more efficacious to identify low oral feeding skills. The POFRAS and SNN Evaluation Protocol failed to discriminate readiness to start oral feeding.